Investment analysis of tobacco farmers' income to ensure sustainability for this industry: A case study for Kelantan and Terengganu / Ahmad Fauzi Puasa ... [et al.] - Puasa, Ahmad Fauzi; Ahmad, Ismariah; Arshad, Najib Lotfy; Ahmad, Ismail (Universiti Teknologi MARA Cawangan Pahang, 2002)
The aim of this paper was to find out the investment analysis for tobacco farmers in Kelantan and Terengganu. This is to ensure that the sustainability of this industry is guaranteed. The level of income from this industry as compared with other crops will determine the continuity of the farming activities. The level of profitability will attract more farmers to venture in this industry. According to the Tobacco Statistics year 2000, Kelantan and Terengganu, the two major tobacco-producing states in the Peninsular Malaysia, have an estimated 14,615 ha or 92.7% of the total tobacco area in the peninsular. For this reason Kelantan and Terengganu have been chosen for data collection. The study focused on the farm investment analysis of the tobacco farmers. There were three types of farmers, namely, the farmers who planted and cured tobacco, the farmers who planted tobacco only, and the farmers who only cured the tobacco leaves. It has been found that the net farm income for those farmers under the supervision of the Lembaga Tembakau Negara (LTN) were earning between RM2,059.39/month to RM2,604.20/month. These farmers not only produced green tobacco leaves but also processed the green (wet) into dried tobacco leaves. On the other hand, those farmers not under LTN supervision only sold their green tobacco leaves to the middleman at a lower price. Their average monthly net farm income was only between RM198.55 and RM446.39. The Kelantan tobacco curers had lost about RM7,692.77/month during the study period while the Terengganu tobacco curers gained about RM702.39/month. The study will look into the yield per plant, the cost incurred per plant, the cost per kilogram of green (wet) and brown (dry) leaves and average profit or loss for all types of tobacco farmers. Besides that, the study also looked at the breakeven analysis for the tobacco curing industries for both Kelantan and Terengganu.